Analisis Pengaruh Car, Npl, Ldr dan Dana Pihak Ketiga Terhadap Profitabilitas Pada PT BPR Sukawati Pancakanti Kecamatan Sukawati - Ni Komang Krisma Dewi; Ni Ketut Sukanti; Nyoman Dwika Ayu Amrita (STIMI Handayani Denpasar, 2023)
This study aims to determine the effect simultaneously or partially on profitability at PT. BPR Sukawati Pancakanti for the period 2013-2020. The sampling technique in this study is to use the saturated sample technique. Data were analyzed using the classic assumption test, multiple linear regression test, determination analysis, simultaneous significance test (F-test), and partial significance test (t-test). The results in this study indicate that CAR, NPL, LDR, and Third Party Funds simultaneously have a significant effect on ROA. CAR have a partially positive and significant effect on ROA. NPL have a partially negative and significant effect on ROA. LDR have a partially positive and significant effect on ROA. Third Party Funds have a partially positive and significant effect on ROA at PT. BPR Sukawati Pancakanti for the period 2013-2020.